Political falsification of history: problems of Anglo-Saxon "Interpretation" - A. A. Vartumyan; M. Yu. Napalkin (Современная наука и инновации, 2023)
The article examines the actual problem of falsification of political history and its "interpretations" by Anglo-Saxon authors. The authors demonstrate a comprehensive approach of a set of methods – from dialectics and gemeneutics to comparative studies and semiotics. The presented principles of dialectics allow us to identify the dynamics of the development of falsifications. The principles of comparative studies used in comparisons with historical facts help to expose falsification. The use of personalism data allows us to more accurately understand the personalities who participated in the falsification. The method of hermeneutics allows you to penetrate into the depth of the meaning of the text, through the disclosure of its true content, the problem of falsifications is represented by the scheme: incompetence-error-lie. The approaches of the US ruling elite to the interpretation of modern international events of political history in relations with Russia have been criticized. In relation to the English falsifiers of history, the authors distinguish two categories of memory: collective and collective. The nature of information wars in fakes and demagogic tricks is revealed. The purpose of further development of this topic is to develop and implement a number of events and "anti-fake" programs based on close interaction of the Russian media, which allow to rid the Russian community of the "weeds" of the Anglo-Saxon falsification of political history.